Energy Efficiency of a Hydraulically Actuated Plastering Machine - Korobko, Bogdan; Zadvorkin, Dmytro; Vasyliev, Ievgen (International Journal of Engineering and Technology, 2018)
The supposition of productivity gain of finishing work using plastering machines has been considered in the article. The work of constituent parts of plastering machines has been studied. The working parameters of the plastering machine has also been calculated. There has been evolved the planning of a three-factor experiment of the second order with the aim of determining the working power, consumed by the mortar pump.Â Â